Exploratory analysis of seaplane operations in Greece: Insights of a survey and SWOT analysis - Andrade, J. F.; Kalakou, S.; Lopes da Costa, R. (European Planning Studies, 2023)
Seaplanes as a transport mode provide the flexibility of using land and water infrastructure for their operations. This functionality presents an opportunity for regions with water surfaces, especially when the sea and air connectivity are the only options. This paper presents an exploratory analysis of seaplanes’ potential as a mode of transport in Greece. After reviewing the topics of air connectivity, remote regions and the coexistence of modes of transport, a survey is designed to collect information on the perspectives of potential users in the Greek region. In total 200 replies of residents and non-residents of the country are collected and reflect a social perspective of seaplane operations. It is found that the main aspects that would motivate passengers to choose seaplanes would be the offered trip duration, the ticket price and the trip convenience. The collected information is used for the elaboration of SWOT analyses that assess seaplane operations at a strategic decision-making level in transport planning and technology management. The analysis concludes that the potential of seaplanes as a transport mode lies on the enhancement of sustainable transport, the connectivity of isolated regions and their economic growth.